KOMBINASI MODEL PBL DAN MAKE A MATCH TERINTEGRASI STEM UNTUK MENINGKATKAN MOTIVASI DAN KARAKTER WASAKA SISWA - Khalisa, Sri Indriyati; Muhsinah Annisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe teacher activities, to analyze activities, motivation, learning outcomes and wasaka characters (environmental care and discipline) in students using a combination model of Problem Based Learning and Make a Match integrated with STEM. This type of research is Classroom Action Research (PTK). The research subjects were VA class students of SDN Sungai Miai 5 Banjarmasin. The results showed that teacher activities were carried out to reach 88.16 with